The Principal Leadership in Developing Inclusive Education for Diverse Students - Shinta Setia; Pwee Leng; Yurillah Endah Mauliate; Dian Ekowati; Dwi Ratmawati (International Journal of Emerging Issues in Early Childhood Education, 2021)
Background – Zonasi, a new ‘zoning-based school’ system implemented by the Indonesian government in June 2019 has created a significatnt impact on student enrollment in all public schools across the country. Before June 2019, student enrollment in public schools were based on its schools selection process, mainly academic achievement, whilst for past 2 years (2019 and 2020) students enrollment has been based on “zonasi”, a geographical distance between student’s home and the chosen school. The closer the distance, the bigger chance to get acceptance. As as result, public schools nowadays has more diverse students than before. Purpose - This research aimed to explore leadership practices of secondary public school principal in transforming a regular public school into inclusive public school through the act of leadership practices. The school was acknowledged by local government and communities as one of the successful inclusive public high school in Surabaya.Design/methodology/approach - This research used a qualitative approach within a case study design. The data collection techniques used in this research were interviews, observations, and school documents. Data were collected from the principal, 2 counseling teachers, 2 special education teachers, and head of educational in the district.Findings - The result revealed four principal leadership behaviour to transform regular public school into inclusive public school i.e. (1) changing mindset the teachers and non-academic staffs, (2) promoting inclusive practices within the school through various programs, (3) promoting inclusive practive in teaching-learning process, (4) building connection with parents & local communities, and seeking government support on the innitiatives.Research limitations – This study only investigated one public school, with the involvement of a school principal and 4 teachers. It would be better if the scope of the research could be broader, for example covering elementary and high schools, and involving more participants, such as the vice principal of the curriculum field, students and parents.Originality/value – This study contributes to leadership research in the context of secondary school education, which has undergone a transformation from the previously students tend to be homogeneous because they are based on standardized academic qualification, nowadays students at schools have more diverse social backgrounds as a result of the implementation of the zoning system in Indonesia. The findings of this paper can be used as a tool. a guide for policy makers and educational planners regarding zoning system in Indonesia. Such practices can also be learned, adapted and imitated by other schools.